Da Vinci Xi™ robot-assisted liver resection - Min Sun; Weisi Li; Cheng Zhang; Shuangxi Li; Fayong Zhou; Yuntao Zhu; Xiaoyang Zhou (Intelligent Surgery, 2022)
Objective: To summarize and think about the surgical process of Da Vinci Xi™ robot-assisted liver resection. Methods: To summarize the clinical data, preoperative preparations, surgical procedures, and postoperative recovery of a patient who underwent Da Vinci Xi™ robot-assisted left hepatectomy in the third ward of the Department of Hepatobiliary and Pancreatic Surgery of the Second Affiliated Hospital of Kunming Medical University in 2021. Discussion to guide future clinical work. Results: The left hemihepatectomy was performed safely and effectively on patients with left intrahepatic bile duct stones with the assistance of Da Vinci Xi™ robot. Conclusion: Da Vinci Xi™ robot's three-dimensional field of vision, stable and flexible manipulator operation and other advantages make it suitable for liver resection surgery.